1990
DOI: 10.1104/pp.93.2.837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of d-myo-Inositol 1,4,5-Trisphosphate on the Electrical Properties of the Red Beet Vacuole Membrane

Abstract: The effect of channel opening in the tonoplast by D-myo-inositol 1,4,5-trisphosphate [lns(1,4,5)P3] has been examined on red beet (Beta vulgaris) vacuoles. Patch-clamp measurements of the vacuolar potential and current were performed on vacuoles isolated in 0.1 micromolar free Ca2+ medium. With vacuoles clamped at +30 millivolts, the lns(1,4,5)P3 induced changes in current were depending on the Ca2+ buffer strength in the external medium.The spontaneous depolarization of vacuoles in which H+-pumps were activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Generation of IP3 during a signaling cascade could lead to the production of IP6 through the action of IPK1 and 2 ( Munnik and Nielsen, 2011 ). Electrophysiological studies employing isolated plant cell vacuoles have shown that application of either IP3 ( Alexandre and Lassalles, 1990 ; Allen and Sanders, 1995 ) or IP6 ( Lemtiri-Chlieh et al , 2003 ) to the cytosolic face of the tonoplast results in outward Ca 2+ currents from the vacuole lumen. Consistent with these patch clamp studies of Ca 2+ currents across the tonoplast, release of caged IP3 ( Lemtiri-Chlieh et al , 2003 ) or IP6 ( Gilroy et al , 1990 ) in intact protoplasts results in cytoplasmic Ca 2+ elevation due to release of Ca 2+ from intracellular stores.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of IP3 during a signaling cascade could lead to the production of IP6 through the action of IPK1 and 2 ( Munnik and Nielsen, 2011 ). Electrophysiological studies employing isolated plant cell vacuoles have shown that application of either IP3 ( Alexandre and Lassalles, 1990 ; Allen and Sanders, 1995 ) or IP6 ( Lemtiri-Chlieh et al , 2003 ) to the cytosolic face of the tonoplast results in outward Ca 2+ currents from the vacuole lumen. Consistent with these patch clamp studies of Ca 2+ currents across the tonoplast, release of caged IP3 ( Lemtiri-Chlieh et al , 2003 ) or IP6 ( Gilroy et al , 1990 ) in intact protoplasts results in cytoplasmic Ca 2+ elevation due to release of Ca 2+ from intracellular stores.…”
Section: Resultsmentioning
confidence: 99%
“…In these signaling pathways, cytosolic IP3 generation on perception of an external stimulus leads to cytosolic Ca 2+ elevation because of activation of IP3-sensitive tonoplast-localized Ca 2+ channels (30); the resulting cytosolic Ca 2+ spike occurs because of release of intracellular Ca 2+ stores. Using plants in which signal-induced IP3 generation is blocked (31), we found no impairment of AtPep3-mediated cytosolic Ca 2+ elevation; these results suggest that IP3-activated release of vacuolar Ca 2+ does not contribute to AtPep-and AtPepR1-mediated Ca 2+ signaling.…”
Section: His-gchismentioning
confidence: 99%
“…Examples for proteins regulated by PtdIns(4,5)P 2 include plant ion channels and ATPases (Cote et al, 1996;Suh and Hille, 2005), plant phospholipase D (Qin et al, 2002), the actin-modifying enzymes profilin, cofilin, and gelsolin (Drobak et al, 1994;Lemmon et al, 2002;Doughman et al, 2003;Wasteneys and Galway, 2003;Wenk and De Camilli, 2004), and mammalian SNARE complex proteins (Vicogne et al, 2006), implying a role for PtdIns(4,5)P 2 in vesicle fusion (Cremona and De Camilli, 2001;Di Paolo et al, 2004;Gong et al, 2005;Milosevic et al, 2005). PtdIns(4,5)P 2 is also the substrate for phospholipase C (PLC), yielding diacylglycerol and the soluble second messenger, inositol 1,4,5-trisphosphate (Berridge, 1983;Meijer and Munnik, 2003), required for Ca 2þ release from internal stores in both animal (Berridge, 1993) and plant cells (Alexandre and Lassalles, 1990;Allen et al, 1995;Sanders et al, 2002). Obviously, regulatory functions described for PtdIns(4,5)P 2 include some of those required for a regulator of growth processes in tip-growing cells.…”
Section: Introductionmentioning
confidence: 99%